Interferencia de voces, historia e ideología en Conversación en la catedral de Mario Vargas Llosa. - González Ruiz, Julio. (University of Ottawa (Canada), 1996)
According to modern criticism, one of the most interesting aspects of Conversacion en la Catedral (1969), is the use of narrative techniques, although very few critics have analyzed this aspect in detail. A central technique in the narrative semiosis of the novel is the interference--in some parts of the novel-of the voices of the characters on the voice of the narrator, and--in other parts--the partial or total avoidance of such an interference. This thesis attempts to fill the gap in the existing critical approaches by studying these interferences or avoidance, and also its contribution to the ideological expression that the narrator-implied author projects in the novel, as well as the reference to the historical reality of Peru (1948-56). The main conclusion of my study supports the proposed thesis: the interference of the voices, or its avoidance, effectively contributes to the expression of the text ideology, which in turn does not limit itself to the textual diegesis, but rather projects itself to the real world of the Peru Odriista. (Abstract shortened by UMI.)
Keywords: Literature, Modern.